An Exploratory Study of Effective Online Learning: Assessing Satisfaction Levels of Graduate Students of Mathematics Education Associated with Human and Design Factors of an Online Course - Lee, Joohi (International Review of Research in Open and Distributed Learning, 2014)
This exploratory research project investigated graduate students’ satisfaction levels with online learning associated with human (professor/instructor and instructional associate) and design factors (course structure and technical aspects) using a survey study. A total of 81 graduate students (master’s students who majored in math and science education) enrolled in an online math methods course (Conceptual Geometry) participated in this study. According to the results of this study, student satisfaction level is closely associated with clear guidelines on assignment, rubrics, and constructive feedback. In addition, student satisfaction level is related to professor’s (or course instructor’s) knowledge of materials.